Hubungan Anak Stunting terhadap Kejadian Karies Ibu Pada Masa Kehamilan Di Wilayah Kerja Puskesmas Sukaindah Kabupaten Bekasi - Siahaan, Sahat Manampin; Oktavira, Alya Dwi; Sari, Multia Ranum (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
The results of Basic Health Research in 2018 show that the prevalence of caries in Indonesia reached 57.6%, including caries in pregnant women. The occurrence of dental caries in pregnant women can occur before pregnancy which is then exacerbated due to the nausea and vomiting that accompanies pregnancy. Indonesia currently also has a nutritional problem that is of concern, namely stunting in children because it has the highest prevalence compared to other nutritional problems. This study aims to find out whether there is a relationship between stunting children and the incidence of maternal caries during pregnancy in the work area of Sukaindah Community Health Center, Bekasi Regency. Methods: The type of research method used is observational analytical research, cross sectional research design, with sample data obtained using the DMF-T index and stunting data originating from the community health center totaling 50 respondents using a total sampling technique. Chi-Square test results show a sig value, =0.001 (P<0.05), which means there is a relationship between stunting children and the incidence of maternal caries during pregnancy, in the work area of the Sukaindah health center, Bekasi district. Reports results related to each research question and statistical analytic. There is an association between child stunting and the incidence of maternal caries during pregnancy, in the working area of Sukaindah health center, Bekasi district.